Effect of knee joint motion for the transfemoral prosthesis in swimming - Motomu NAKASHIMA; Ayako ONO; Takashi NAKAMURA (Journal of Biomechanical Science and Engineering, 2015)
The objective of this study was to investigate the effect of knee joint motion on swimming performance for a transfemoral prosthesis in swimming. A flat spring at the knee joint was introduced into a prosthesis which had already been developed, in order to enable the knee joint to move according to the fluid force acting on the lower limb. A swimming experiment, in which a subject using the prosthesis swam in a pool, was conducted. Five types of flat spring for the knee joint were prepared for the experiment. From the experiment, it was found that there was a proper stiffness of the flat spring from which the subject felt comfortable during swimming. Next, simulations for the flutter kick and crawl stroke were conducted. The validity of the simulation method was confirmed since the simulated joint angles in the simulation of the flutter kick were sufficiently consistent with the experimental ones in respect to the amplitudes and phases for both the knee and ankle. During the simulation of the crawl stroke, it was found that the amplitude of the hip joint torque on the prosthetic leg compared to the healthy leg increased according to the increase in the stiffness of the knee joint. Since this amount was considered to directly correspond with the ‘reaction during kick' in the VAS evaluation of the experiment, in which the subject evaluated the stiffer knee flat spring as ‘heavier', the consistency of the tendencies between the simulation and experiment was confirmed. From the simulation results, it was also suggested that the subject in the experiment preferred stiffness at the knee joint which minimized the difference between the amplitude of the hip joint torque on the healthy leg and that on the prosthetic leg.